Representation, resistance and the digiqueer: fighting for recognition in technocratic times - Ellis, Justin R. (Bristol shorts research, 2023)
"Digital media technologies have enabled some LGBTQ+ individuals and communities to successfully organize for basic rights and justice. But these technologies can also present risks, such as online and in-person harassment and assault, and unsettled standards of privacy and consent. Justin R. Ellis provides new insights on LGBTQ+ identity formation through social media networks and platform biometrics. Drawing on debate over gender, procreation, religion, nationalism and tech-regulation, he considers the effects of surveillance technologies on LGBTQ+ agency. In doing so, he brings an interdisciplinary 'digiqueer' perspective to negotiations of LGBTQ+ identity through case studies of digital harms from case law, parliamentary debates, social and mainstream media and LGBTQ-tech advocacy."--Page 4 of cover